Student resource and readings manual for use with personal finance - Kapoor, Jack R. (McGraw-Hill Education, 1996)
This publication is designed to help you learn and apply personal financial planning concepts. This Student resource and readings manual supplements personal finance and will guide you through the content of the book. You will be given opportunities to learn, test and apply personal financial topics.